Holistic Management of Dyslipidemia in a Geriatric Patient with Comorbid Hypertension and History of Hyperuricemia Following Lower Extremity Trauma - Muhammad Hatta; Agustina Hadjar; Muhammad Iqbal Pratama; Muhammad Irham Fadil Al Muhsin; Muhammad Yusuf Al Afif; Muhammad Zaidan Afkar; Mutiara Salsabila (Biomedical Research and Theory Letters, 2026)
Dyslipidemia is a major metabolic disorder and a key risk factor for atherosclerotic cardiovascular disease (ASCVD), particularly in the geriatric population. Elderly patients frequently present with multiple comorbidities, such as hypertension and hyperuricemia, which complicate clinical management and substantially increase cardiovascular risk. Moreover, acute conditions, including trauma-related injuries, may further disrupt metabolic control, functional capacity, and adherence to long-term therapy. This case report describes a 70-year-old male patient (RE) who presented to a primary healthcare center with swelling and intermittent pain in the right lower extremity following a fall. The patient had a known history of dyslipidemia, hypertension, and hyperuricemia. Laboratory investigations revealed elevated total cholesterol (242 mg/dL), borderline fasting plasma glucose (102 mg/dL), and uric acid level of 6.6 mg/dL. Physical examination was unremarkable except for edema and localized tenderness in the affected limb, consistent with a soft tissue injury. A holistic management approach was implemented, integrating pharmacological and non-pharmacological interventions. Statin therapy was initiated to address dyslipidemia, antihypertensive treatment was optimized, and analgesic therapy combined with limb elevation was provided to manage acute pain and edema. Non-pharmacological strategies included comprehensive lifestyle modification, encompassing dietary counseling (low saturated fat, low salt, and low purine diet), gradual resumption of physical activity following injury recovery, and structured patient–family education to improve adherence and prevent recurrent falls. Follow-up evaluation demonstrated clinical improvement, including resolution of edema, improved functional mobility, and better metabolic control. The novelty of this case lies in demonstrating how acute trauma in geriatric patients can act as a critical entry point for integrated chronic disease management within primary care settings. This case emphasizes that holistic, biopsychosocial–spiritual management not only improves lipid and blood pressure control but also enhances functional outcomes and quality of life in elderly patients with complex comorbidities.